Motivational telephone intervention to risk gamblers by a state-owned gambling operator in Sweden - Hakansson, Anders; Franklin, Katja; Dahlström, Maria; Lyckberg, Axel (Frontiers in Psychiatry, 2024)
Background and aims Few studies have tested the effect of a motivational telephone intervention from a gambling operator to clients with high-risk gambling practices. This study aimed to study subsequent limit setting, self-exclusions and gambling post-intervention, compared to controls. Methods The study assessed a motivational, personalized telephone intervention by the state-owned Swedish gambling operator AB Svenska Spel within its subsection of sports, poker, online casino and bingo gambling. Clients successfully reached with the telephone intervention (n = 1,420) were compared to clients who could not be reached (n = 1,504). Gambling practices during 8 weeks pre-intervention were assessed, and outcome measures limit setting, self-exclusion, and gambling 4 weeks post-intervention. Results The telephone intervention was associated with increased limit settings (10 vs. 5 percent, p < 0.001), self-exclusions (11 vs. 8 percent, p < 0.01), lowered theoretical losses (p < 0.001), but not significantly associated with gambling abstinence (18 vs. 15 percent, p = 0.07). In unadjusted analyses of sub-groups, significant associations of the intervention with full gambling abstinence were seen in people who gamble on online casino/bingo (19 vs. 14 percent, p < 0.01), but not in sports bettors. In logistic regression, the intervention was not associated with full week 1–4 abstinence. Conclusion A personalized motivational telephone intervention to people displaying high-risk gambling, delivered by a gambling operator, is promising, and effects were seen on the uptake of responsible gambling tools post-intervention. Effects may be more pronounced in users of chance-based, online games, than in sports bettors.